Suppressed glycolytic metabolism in the prostate of transgenic rats overexpressing calcium-binding protein regucalcin underpins reduced cell proliferation - Vaz, CV (2019)
Regucalcin (RGN) is a calcium-binding protein underexpressed in human prostate cancer cases, and it has been associated with the suppression of cell proliferation and the regulation of several metabolic pathways. On the other hand, it is known that the metabolic reprogramming with augmented glycolytic metabolism and enhanced proliferative capability is a characteristic of prostate cancer cells. The present study investigated the influence of RGN on the glycolytic metabolism of rat prostate by comparing transgenic adult animals overexpressing RGN (Tg-RGN) with their wild-type counterparts. Glucose consumption was significantly decreased in the prostate of Tg-RGN animals relatively to wild-type, and accompanied by the diminished expression of glucose transporter 3 and glycolytic enzyme phosphofructokinase. Also, prostates of Tg-RGN animals displayed lower lactate levels, which resulted from the diminished expression/activity of lactate dehydrogenase. The expression of the monocarboxylate transporter 4 responsible for the export of lactate to the extracellular space was also diminished with RGN overexpression. These results showed the effect of RGN in inhibiting the glycolytic metabolism in rat prostate, which was underpinned by a reduced cell proliferation index. The present findings also suggest that the loss of RGN may predispose to a hyper glycolytic profile and fostered proliferation of prostate cells.